Frequency domain analysis using MATLAB app designer - Rex, Mercy (Nanyang Technological University, 2024)
This project entails building an interactive application for students learning Signals and Systems. Signals and Systems is an educational module which is widely studied by engineering students. It equips them with basic concepts of signal processing and analysis which is vital for application in advanced concepts and requires a deep understanding of signals. This application will allow users to plot various types of graphs to visualize. The concepts of Fourier series and Fourier transform will be performed on these graphs. Users can learn from the resultant spectra to comprehend the contents of the course. This will enable them to engage in more effective learning.